143 CASE PRESENTATION: CASTLEMAN'S DISEASE INVOLVING THE ORBIT. (10th December 2015) - Baker, J.; Kim, D.; Hamilton, R. D.
Abstract : A 27-year-old black female presented with complaints of gradually worsening headaches and right eye pain; no constitutional symptoms. After failure of therapies for migraine headaches, periorbital cellulitis, and depression, she was evaluated by an ophthalmologist, who discovered a mass in the superomedial aspect of the right eye. Prednisone was initiated for presumed scleritis; excisional biopsy revealed a lesion consisting of lymphocytes, plasma cells, and histiocytes concentrated around vessels without scleral infiltration. "Onion skin" appearance of angiocentric lymphocytes was determined to be consistent with Castleman's disease, hyaline vascular variant. Metastatic workup including MRI of the brain and CT scan of the chest, abdomen, and pelvis was unremarkable. CBC, serum chemistries, renal function, and liver panel were within normal limits. A test for HIV antibody was negative. After complete excision, she was continued on high-dose prednisone with the addition of azathioprine and corticosteroid eye drops. She has responded well to this therapy aside from the expected complications of steroid therapy, including weight gain and hyperglycemia. Discussion: Castleman's disease is a rare lymphoproliferative disorder associated with human immunodeficiency virus (HIV), human herpesvirus eight (HHV-8), and malignancies such as lymphoma and Kaposi's sarcoma. Histological variants include hyaline vascular, plasma cell, and mixed subtypes. Localized disease is unicentric, consisting of a solitary mediastinal mass. Eighty percent of unicentric cases are of hyaline vascular histology. Multicentric disease describes patients with generalized lymphadenopathy and systemic symptoms. This variant is frequently associated with an aggressive clinical course, infection with HIV or HHV-8, and plasma cell or mixed histology. Patients who require systemic therapy are generally treated with corticosteroids, steroid-sparing azathioprine or cyclosporine, antiviral agents, or chemotherapy. The various chemotherapy regimens used have included single-agent chlorambucil, vinblastine, rituximab, or etoposide with the multiagent lymphoma regimens CVP or CHOP. A patient with bilateral, orbital, multicentric Castleman's disease was remitted with rituximab in an earlier report. Surgical excision, radiation therapy with conventional electrons or protons, and systemic chemotherapy are options for treatment, with careful explanation of risks and side effects.